Enhanced photoelectrochemical activities for water oxidation and phenol degradation on WO3 nanoplates by transferring electrons and trapping holes - Sun, Liqun; Wang, Yuying; Raziq, Fazal; Qu, Yang; Bai, Linlu; Jing, Liqiang (Scientific reports, 2017)
It is highly desired to improve the photoelectrochemical (PEC) performance of nanosized WO 3 by artificially modulating the photogenerated electrons and holes simultaneously. Herein, WO 3 nanoplates have been successfully prepared by a simple one-pot two-phase separated hydrolysis-solvothermal method, and then co-modified with RGO and phosphate acid successively by wet chemical processes. Subsequently, the as-prepared WO 3 -based nanoplates were immobilized on the conductive glasses to explore the PEC activities for both water oxidation to evolve O 2 and phenol degradation. It is clearly demonstrated that the co-modified WO 3 nanoplates exhibit significantly improved PEC activities compared with pristine WO 3 , especially for that with the amount-optimized modifiers by ca. 6-time enhancement. Mainly based on the evaluated hydroxyl radical amounts produced and the electrochemical impedance spectra, it is suggested that the improved PEC activities are attributed to the greatly enhanced photogenerated charge separation after chemically modification with RGO and phosphate groups to WO 3 , respectively by transferring electrons as the collectors and trapping holes via the formed negative field after phosphate disassociation. This work provides a feasible synthetic strategy to improve the photoactivities of nanosized WO 3 for energy production and environmental remediation.